Primary Care Service Utilization Among People at High Risk of Fatal Opioid Overdose: A Short Communication on an Autopsy Study - Matthew Jones; Ceri Bradshaw; Jenna Jones; Ann John; Helen Snooks; Alan Watkins (SAGE Publishing, 2020)
Objectives: We sought to explore the sociodemographics and primary care service utilization among people who died from opioid overdose and to assess the possibility of using this information to identify those at high risk of opioid overdose using routine linked data. Methods: Data related to decedents of opioid overdose between January 1, 2012 and December 31, 2015 were linked with general practitioner (GP) records over a period of 36 months prior to death. Results: Of n = 312 decedents of opioid overdose, 73% were male (n = 228). Average age at death was 40.72 (SD 11.92) years. A total of 63.8% of the decedents were living in the 2 most deprived quintiles according to the Welsh Index of Multiple Deprivation. Over 80% (n = 258) of the decedents were recorded as having at least 1 GP episode during the 36-month observation period prior to death. The median number of episodes per decedent was 75 [38-118]. Overall, 31.8% (n = 82) of decedents with at least 1 GP episode received a prescription for a proton pump inhibitor and 31% (n = 80) were prescribed a broad-spectrum antibiotic. According to their GP records, less than 10% were referred to or receiving specialist drug treatment (n = 24, 9.3%); or were known to be drug dependent (n = 21, 8.14%), or a drug user (n = 5, 1.94%). In all, 81% were recorded as smokers (n = 209) and 10.5% as ex-smokers (n = 27). Conclusions: The majority of decedents of opioid overdose were in contact with GP services prior to death. GPs are either often unaware of high-risk opioid use, or rarely record details of opioid use in patient notes. It is possible that GP awareness of high-risk opioid use could be increased. For example, awareness of the risks associated with opioid use, and the relationship between the sociodemographic and clinical characteristics of opioid overdose decedents could be raised using educational materials prominently displayed in waiting areas. Clinicians in primary care may be in an excellent position to intervene in problematic opioid use.